Mathematical Literacy Seen from Cognitive Style in Learning of Auditory Intellectually Repetition Model with Constructivism Approach Assisted by Google Classroom - Elis Fitria Herliani; Wardono Wardono; Budi Waluya (Unnes Journal of Mathematics Education Research, 2022)
This study aims to describe mathematical literacy seen from cognitive style in learning of Auditory Intellectually Repetition model with constructivism approach assisted by google classroom. This research is a type of qualitative research. The approach used in this study is a descriptive approach. The subjects in this study were class VIII G of SMP Negeri 1 Welahan. Subjects were chosen by each of the 5 students based on the type of cognitive style Field Independent (FI) and type cognitive style Field Dependent (FD). Data collection is done by Group Embedded Figure Test (GEFT), interview guide, and observation. The results of this study indicate that students with a cognitive style Field Independent (FI) capable of the mathematical literacy component communication, mathematizing, representation, and using symbolic, formal, and technical language and operation. Less capable on components devising strategies for solving problems. sufficient on components using mathematics tools. Then students with type cognitive style Field Dependent (FD) is sufficient of the mathematical literacy component communication, devising strategies for solving problems, using symbolic, formal, and technical language and operation. Then less able on components mathematizing, representation, reasoning and argument, using mathematics tools.